Peningkatan Keaktifan Siswa Dalam Pembelajaran Matematika Melalui Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT): Increasing Student Activity in Mathematics Learning through the Application of the Teams Games Tournament (TGT) Type Cooperative Learning Model - Mohammad, Mohammad (Jurusan Pendidikan Teknik Elektro, 2025)
This study aims to improve student activeness in mathematics learning through the application of the cooperative learning model of the teams games tournament (TGT) type in class X.II of SMA Negeri 17 Makassar in the 2024/2025 academic year. This study uses Classroom Action Research which is carried out in two cycles with 36 students as research subjects. Data collection methods include observation sheets and student learning activity questionnaire sheets. Based on the results of the study, using the TGT type learning model can increase student activeness in mathematics learning. Based on data analysis, student learning activity increased by 42,9%, up from 60.2% in cycle I to 80.1% in cycle II.